2008
DOI: 10.1177/0748233708100090
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in the liver and kidney tissues of Wistar albino rat exposed to fenitrothion

Abstract: The aim of this study was to investigate the dose-related effects of fenitrothion (FNT) on the liver and kidney. The study was conducted on 8-week-old male Wistar rats that were divided into four groups (three experimental groups and one control group) and were treated orally with different doses (25, 50, 100 mg/kg) of FNT for 28 consecutive days. After treatment, the rats were anesthetized with ether and liver and kidney samples were taken for histological studies. The results showed that the histopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 4 publications
10
29
0
1
Order By: Relevance
“…Current study also showed dilatation, vacuolation, and brush border loss of tubule cell. These findings also relevant to study by Ogeturk (2005), Adewole (2007), and Ashafar (2008), which showed similar damage on tubule cell of wistar rats after CCl 4 administration.…”
Section: Resultssupporting
confidence: 79%
“…Current study also showed dilatation, vacuolation, and brush border loss of tubule cell. These findings also relevant to study by Ogeturk (2005), Adewole (2007), and Ashafar (2008), which showed similar damage on tubule cell of wistar rats after CCl 4 administration.…”
Section: Resultssupporting
confidence: 79%
“…Moreover, fenitrothion and dichlorvos are a contactacting organophosphate insecticide which inhibits acetylcholinesterase activity, thus disrupting the nervous system [24][25][26][27][28] . The pattern of cholinesterase inhibition was in good agreement with the probable runoff of pesticides from agricultural fields [29,30] .…”
Section: Sub-acute Toxicitymentioning
confidence: 99%
“…Each dose from both compounds was dissolved in 0.5 mL water and was administered orally to rats using stomach tube with ball tipped oral incubated needle. The LD 50 value of the two compounds was calculated, for 24 h. mortalities following each treatment.…”
Section: Ld 50 Determinationmentioning
confidence: 99%
“…There are four categories of damage level based on semi quantitative scale (Di Giulio & Hinton, 2008;Afshar, et al, 2008; Safahieh, et al, 2012). They are: (-) = none; (+) = mild (achieving 25% in 1 visual field); (++) = moderate (achieving 50 % in 1 visual field); and (+++) = severe (achieving75% -100% in 1 visual field).…”
Section: Histology Proceduresmentioning
confidence: 99%
“…They are fixation, dehydration, clearing, infiltration, embedding, sectioning, affixing, defarafinisation, staining, mounting, and labeling. Observation and calculation of the amount of liver organ cell in tissue was done with binocular microscope Olympus BX41 with 400 times of zooming in and photographing using digital camera Olympus CX21FS1.There are four categories of damage level based on semi quantitative scale (Di Giulio & Hinton, 2008;Afshar, et al, 2008; Safahieh, et al, 2012). They are: (-) = none; (+) = mild (achieving 25% in 1 visual field); (++) = moderate (achieving 50 % in 1 visual field); and (+++) = severe (achieving75% -100% in 1 visual field).…”
mentioning
confidence: 99%